2018
DOI: 10.1038/s41419-018-0404-5
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-induced killer cells as a feasible adoptive immunotherapy for the treatment of lung cancer

Abstract: Most of the patients with lung cancer are diagnosed at advanced stage, and they often lose the opportunity of surgical therapy, most of whom fail to reach good prognosis after chemotherapy. Recently, a few clinical studies have confirmed the role of adoptive T-cell transfer in the maintenance therapy of cancer patients. Here, we provided statistical insights into the role of CIKs in advanced lung cancer from three different levels, cell model (in vitro co-culture system), mice model (in situ lung cancer), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In one recent study, Chen and colleagues found DC-activated CIK cells in combination with standard platinum-based doublet chemotherapy to be well tolerised and to significantly improve 3-year survival compared to chemotherapy alone in NSCLC patients (50.7% vs 33.8%, P = 0.036, n = 68/group). 42 Other forms of ACT have become an area of increased interest in lung oncology research. A randomised phase-III clinical trial (n = 101) assessed the efficacy of DC-activated CTL adoptive transfer combined with standard platinum-based chemotherapy for post-surgical NSCLC patients.…”
Section: Adoptive Cell Transfermentioning
confidence: 99%
“…In one recent study, Chen and colleagues found DC-activated CIK cells in combination with standard platinum-based doublet chemotherapy to be well tolerised and to significantly improve 3-year survival compared to chemotherapy alone in NSCLC patients (50.7% vs 33.8%, P = 0.036, n = 68/group). 42 Other forms of ACT have become an area of increased interest in lung oncology research. A randomised phase-III clinical trial (n = 101) assessed the efficacy of DC-activated CTL adoptive transfer combined with standard platinum-based chemotherapy for post-surgical NSCLC patients.…”
Section: Adoptive Cell Transfermentioning
confidence: 99%
“…For the treatment of lung cancer, surgery, chemotherapy and radiotherapy are still the primary choice in the clinic. In recent years, immunotherapy and targeted therapy are gradually developed and bring great potential for these patients, such as cytokine-induced killer cells [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, anti-angiogenic effects are modulated through multiple pathways. The key signalling pathway that modulates proliferation of endothelial cells is the vascular endothelium growth (50)(51)(52)(53)(54). In this study, CIK cells were generated by culturing peripheral blood monocytes isolated from healthy donors with interferon-gamma (IFN-) and interleukin-2.…”
Section: Anti-cancermentioning
confidence: 99%